2013
DOI: 10.3928/01477447-20130821-21
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Implants of Differing Metallic Composition in the Treatment of Upper-extremity Fractures

Abstract: Mixing implants with differing metallic compositions has been avoided for fear of galvanic corrosion and subsequent failure of the implants and of bone healing. The purpose of this study was to evaluate upper-extremity fractures treated with open reduction and internal fixation with metallic implants that differed in metallic composition placed on the same bone. The authors studied the effects of using both stainless steel and titanium implants on fracture healing, implant failure, and other complications asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The reconstruction of large bone defects has traditionally been achieved by the use of resorbable bone substitutes [ 14 , 26 ] or permanent metallic prosthetic implants [ 15 , 18 , 19 ]. Unlike bone substitutes, which cannot hold the load bearing, metal prosthetic implants allow early functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstruction of large bone defects has traditionally been achieved by the use of resorbable bone substitutes [ 14 , 26 ] or permanent metallic prosthetic implants [ 15 , 18 , 19 ]. Unlike bone substitutes, which cannot hold the load bearing, metal prosthetic implants allow early functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to titanium implants, stainless steels exhibit a lower strength and corrosion resistance and a greater ductility and stiffness. Their high stiffness makes stainless-steel implants inferior to titanium ones in bone replacement applications [ 15 ]. Currently, titanium is the most used metallic biomaterial due to its biocompatibility, resistance to the corrosive activity of the body, and its specific force related to its traction force and rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of this phenomenon is not agreed on in the scientific community, as many clinical studies have not shown galvanic corrosion of mixed metals to be clinically significant. [456] This report, however, argues otherwise.…”
Section: Discussionmentioning
confidence: 80%
“…Despite fixation systems are made of different metallic compositions, if the corrosion were of real clinical concern, more complications would have occurred related to the dissimilar metals in the same biological milieu [21]. Furthermore, the current flowing through the galvanic couple is very low [22].…”
Section: Discussionmentioning
confidence: 99%